STUDY OF TOTAL SUSPENDED MATTER TRANSPORTATION AND CIRCULATION IN JAKARTA BAY USING NUMERICAL SIMULATION AND SATELLITE DATA - Suriwati, Luh Made; Osawa, Takahiro; Mahendra, Made Sudiana (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 5 No 1)
Jakarta Bay lies in the north of Jakarta and receives freshwater run off from thirteen rivers that run through the Jakarta metropolitan area, a conurbation that is home to some 20 millions people. Total discharges of organic water pollution have experienced a rapid increase from 214 tones per day in 1980 to over 537 tones per day in 1993. This is resulted to the high nutrient levels and eutrophication of coastal waters. Input pollutant in Jakarta Bay change the natural environment condition. Eutrophication has severe local impacts in the Jakarta Bay (GEF, 2008). Study of TSM in Jakarta Bay was conducted during September 2008 to June 2009. The aims of this research were to investigate the transportations of TSM in Jakarta Bay MODIS satellite data was used and the current pattern circulation in Jakarta Bay. Methods applied were MODIS satellite data analyses from 2003 to 2005 and numerical model 2-dimensional, for the in-situ data of total suspended matter secondary data from LIPI in September 2004 was applied. To validate the result regression method was used. Validation research results using MODIS satellite analysis showed the regression coefficient is R=0.72. Vector of current in Jakarta Bay in September 2004 experienced of the change direction and speed at each condition during spring condition at flood tide 1.23 m/s, highest tide 0.77 m/s, ebb tide 0.83 m/s, and lowest tide1.31 m/s and during neap condition at flood tide 0.71 m/s, highest tide 0.69 m/s, ebb tide 0.90 m/s, and lowest tide 0.34 m/s. Transportation of TSM in Jakarta Bay are dynamic, in dry season transportation of TSM higher than rain season.
Keywords: Remote sensing, Total Suspended Matter, Jakarta Bay